말기신부전증 환자의 좌심실 비대에 대한 심초음파도 연구 - 이상호; Sang Ho Lee; 유혜영; Hye Young Ryu; 송민수; Min Su Song; 강흥성; Hung Sun Kang; 홍성표; Seoung Pyo Hong; 이태원; Tae Won Lee; et al. (The Korean journal of medicine, 1998)
Objective: Left ventricular hypertrophy is common and major complication in patients with end stage renal disease(ESBD), but pathogenesis is not clear. We have used echocardiography to evaluate influential factors and contractile performance according to the geometry of left ventricle. Methods: We measured left ventricular mass, the extent of pericardial effusion and systolic function of left ventricle with M-mode and two dimensional echocardiography in 99 cases of ESRD from March 1993 to March 1996. Results: 1) Body surface area and systolic blood pressure was higher in men than those in women. But, there was no difference in LV mass index or systolic function between the sex. 2) Among the 99 patients with ESRD, 89 cases(90%) had increased ventricular mass and 10 cases had normal ventricular mass. In the left ventricular hypertrophy groups, 60 cases had concentric hypertrophy, 29 cases had eccentric hypertrophy. 3) In patients with normal ventricular mass, hypertension and pericardial effusion were less frequent than in those with left ventricular hypertrophy. In patients with concentric hypertrophy, systolic blood pressure and body surface area were increased and serum albumin was decreased as compared to patients with eccentric hypertrophy. In patients with eccentric hypertrophy, duration of dialysis was increased. But, the result of Logistic analysis showed that systolic blood pressure and serum albumin were reliable factors for the geometry of left ventricle. 4) In patients with eccentric hypertrophy, LV mass index was significantly correlated with the concentration of serum alkaline phosphatase and phosphate. But, in patients with concentric hypertrophy, any factors were not correlated with LV mass index. 5) Systolic performances such as ejection fraction and fractional shorter were decreased in patients with eccentric hypertrophy. 6) The pattern of left ventricular hypertrophy was not different among non-dialysis group, hemodialysis group and CAPD group. Conclusion: In patients with ESHD, left ventricular hypertrophy is a common complication and most common hypertrophic type is concentric hypertrophy. The geometry of left ventricular hypertrophy may be influenced by various factors such as systolic blood pressure and serum albumin concentration and influence on the systolic performance of left ventricle. urther study for the geometry of left ventricle and the prognosis may be necessary for the improvement of cardiovascular complications in patients with ESRD.